Low-temperature low-power-consumption manganese zinc ferrite material and preparation method thereof

By adding specific auxiliary components and mineralizers to the manganese zeolite material, combined with high-temperature roasting and two-step atmosphere treatment, the low-temperature power consumption of the material is reduced, and the magnetic conduction of manganese zeolite material in a low-temperature environment is solved. The problem of decreasing rate and increasing hysteresis loss has achieved stable operation of new energy vehicles at extremely low temperatures.

CN119241224APending Publication Date: 2025-01-03SHANDONG CHUNGUANG MAGNETOELECTRIC TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411399213.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The permeability of manganese-zeb ferrite materials decreases in low temperature environments and increase hysteresis loss, resulting in unstable operation of new energy vehicles at extremely low temperatures, posing safety hazards.

Method used

The formula of manganese zinc ferrite material with low temperature and low power consumption includes the main components Fe2O3, ZnO and Mn3O4, auxiliary components CaO, SiO2, Nb2O5, Co2O3, TiO2, SnO2, mineralizers WO3 and Bi2O3, and the mineralizers WO3 and Bi2O3 are made by high-temperature roasting and spraying. Preparation of particle and two-step atmosphere treatment method reduces magnetocrystal anisotropy and hysteresis loss and improves resistivity.

Benefits of technology

It significantly reduces the power consumption of manganese-zeb ferrite materials at -40℃~0℃, improves the wide-temperature and low-power consumption characteristics of the materials, and ensures that new energy vehicles work at extremely low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241224A_ABST
    Figure CN119241224A_ABST
Patent Text Reader

Abstract

The invention provides a low-temperature low-power-consumption manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is prepared from main components, auxiliary components and a mineralizer, the main components comprise, by mole percentage, 53.5%-55.5% of Fe2O3, 8.5%-11.5% of ZnO and the balance Mn3O4, and the total percentage is 100%; the auxiliary component is composed of CaO, SiO2, Nb2O5, Co2O3, TiO2 and SnO2, and the mineralizing agent is composed of WO3 and Bi2O3. The low-temperature power consumption characteristic of the material is improved by reducing the magnetocrystalline anisotropy of the power manganese-zinc ferrite material. According to the present invention, the iron passing formula is adopted as the main formula, the doped oxide capable of improving magnetocrystalline anisotropy is matched so as to improve the low-temperature magnetocrystalline anisotropy constant of the power manganese zinc ferrite material, and the oxide capable of improving magnetocrystalline anisotropy and the oxide capable of improving resistivity are matched so as to achieve the low-temperature and low-power consumption effect;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ferrite materials, and in particular to a low-temperature and low-power consumption manganese-zinc ferrite material and a preparation method thereof. Background Art

[0002] Manganese-zinc ferrite is widely used in various electronic devices such as transformers, inductors, switching power supplies, filters, power dividers, couplers, antennas, sensors, etc. due to its high magnetic permeability, high saturation flux density Bs and low power loss. As a widely used basic electronic material, manganese-zinc ferrite plays an indispensable role in the power conversion process of electric vehicles and is widely used in new energy vehicle OBC equipment, EV charging equipment, HEV system power conversion, DC-DC converters, battery management systems, power distribution units, etc. The performance of MnZn ferrite is often no longer required to have a single indicator, such as low power consumption or high magnetic permeability; higher requirements are put forward for the temperature performance of such devices, especially in order to adapt to cold environments such as northern my country, such as requiring the device to work normally in an environment of -40C to 120°C.

[0003] In a low temperature environment, the magnetic permeability of manganese-zinc ferrite will drop significantly due to the influence of the material's magnetocrystalline anisotropy, and the hysteresis loss will increase significantly. The manganese-zinc ferrite material in the related art maintains very low losses at 20-140°C. However, after the temperature is lower than 20°C, the material loss begins to increase significantly, and after the temperature reaches below 0°C, the loss increases sharply. For new energy vehicles working in cold areas, their operating temperature deviates from 25-140°C, reaching -30°C or even -40°C. At such a low temperature, the loss of conventional power ferrite materials is very high, and new energy vehicles using this type of material are difficult to start, and the car has a greater safety hazard. Therefore, it is necessary to reduce the power consumption of manganese-zinc ferrite at low temperatures to ensure the working stability of new energy vehicles at extremely low temperatures. Summary of the invention

[0004] The present application provides a low-temperature and low-power consumption manganese-zinc ferrite material and a preparation method thereof, so as to solve the problem that the magnetic permeability of manganese-zinc ferrite will be greatly reduced due to the influence of the magnetic crystal anisotropy of the material, and the hysteresis loss will be greatly increased, thereby reducing the power consumption of manganese-zinc ferrite at low temperatures to ensure the working stability of new energy vehicles at extremely low temperatures.

[0005] In the first aspect, the present application provides a low-temperature and low-power manganese-zinc ferrite material, which is composed of a main component, an auxiliary component and a mineralizer; the main component is in molar percentage: 53.5-55.5% Fe2O3, 8.5-11.5% ZnO, and the remainder is Mn3O4, totaling 100%; the auxiliary component is composed of CaO, SiO2, Nb2O5, Co2O3, TiO2, and SnO2. Based on the total weight of the main components, the auxiliary components are in mass percentage: CaO is 0.01-0.05%, SiO2 is 0.05-0.1%, Nb2O5 is 0.01-0.03%, Co2O3 is 0.3-0.6%, TiO2 is 0.05-0.1%, and SnO2 is 0.05-0.1%; the mineralizer is composed of WO3 and Bi2O3.

[0006] In some possible implementations, based on the total weight of the main components, the mineralizer is in the following mass percentages: WO3 is 0.01-0.05%, and Bi2O3 is 0.02-0.06%.

[0007] In a second aspect, the present application provides a method for preparing a low-temperature and low-power consumption manganese-zinc ferrite material, the preparation method comprising:

[0008] Weigh iron oxide, manganese tetraoxide and zinc oxide, put them into a sand mill, add deionized water, mix and dry to obtain a mixed dry material;

[0009] The mixed dry material is subjected to high temperature roasting, and the mixed dry material after high temperature roasting is mixed with auxiliary components and a mineralizer to obtain a sand-grinding powder, and the sand-grinding powder is put into a sand mill to obtain a sand-grinding slurry;

[0010] The sanding slurry is mixed with a binder, spray granulated and pressed to obtain a blank;

[0011] Pre-sintering the blank;

[0012] The pre-sintered blank is sintered to obtain a sintered material, and the sintered material is subjected to a two-step atmosphere treatment method for heat preservation to obtain a manganese-zinc ferrite material.

[0013] In some possible implementations, pre-sintering the blank includes:

[0014] The pressed blank is pre-sintered in an atmosphere protection bell furnace, wherein during the pre-sintering process, the temperature is raised to 200° C. at a rate of 1 to 4° C. / min, and then raised to 300 to 350° C. at a rate of 0.5 to 1° C. / min.

[0015] In some possible implementations, sintering the pre-sintered blank to obtain a sintered material includes:

[0016] When the pre-sintered blank is sintered, the temperature in the atmosphere protection bell furnace is raised to 1100-1150° C. at a heating rate of 2-4° C. / min;

[0017] In a nitrogen atmosphere with an oxygen content of 0.01 to 0.05%, the temperature in the atmosphere protection bell furnace is raised to 1250 to 1350° C. at a heating rate of 4 to 8° C. / min;

[0018] After the temperature reaches 1250-1350°C, keep it in a nitrogen atmosphere with an oxygen content of 0.005·0.01% for 2-4 hours;

[0019] The oxygen content of the atmosphere protection bell furnace is adjusted, and the temperature is kept in a nitrogen atmosphere with an oxygen content of 2 to 5% for 1 to 3 hours.

[0020] In some possible implementations, the sintering material is treated with a two-step atmosphere treatment method for heat preservation, including:

[0021] After the insulation is completed, the temperature in the atmosphere protection bell furnace is reduced to 1000°C to 1100°C at a cooling rate of 0.3 to 1.0°C / min; wherein the oxygen content of the atmosphere corresponding to 1100°C is 0.3 to 0.6%, the oxygen content of the atmosphere corresponding to 1050°C is 0.05 to 0.1%, and the oxygen content of the atmosphere corresponding to 1000°C is 0.02-0.05%;

[0022] When the temperature in the atmosphere protection bell furnace reaches 1000°C to 1100°C, the temperature in the atmosphere protection bell furnace is cooled to 200°C at a cooling rate of 5 to 10°C / min in a nitrogen atmosphere with an oxygen content of less than 50 ppm.

[0023] In some possible implementations, the temperature for high-temperature roasting the mixed dry material is 850-950° C., and the high-temperature roasting time is 1-4 hours.

[0024] In some possible implementations, the weight of deionized water added to the sand mill is 50-100% of the weight of the sand-grinding powder, the sand-grinding time is 2-4 hours, and the laser particle size D50 of the sand-grinding powder is about 1.0-1.5 μm.

[0025] In some possible implementations, the binder is polyvinyl alcohol, and the amount of the polyvinyl alcohol is 0.1% to 0.5% by weight of the sanding slurry.

[0026] In some possible implementations, the blank density is 3.0-3.2 kg / cm 3 .

[0027] From the above content, it can be seen that the present application provides a low-temperature and low-power manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material is composed of a main component, an auxiliary component and a mineralizer; the main component is in molar percentage: 53.5-55.5% Fe2O3, 8.5-11.5% ZnO, and the remainder is Mn3O4, totaling 100%; the auxiliary component is composed of CaO, SiO2, Nb2O5, Co2O3, TiO2, and SnO2. Based on the total weight of the main components, CaO is 0.01-0.05%, SiO2 is 0.05-0.1%, Nb2O5 is 0.01-0.03%, Co2O3 is 0.3-0.6%, TiO2 is 0.05-0.1%, and SnO2 is 0.05-0.1%; the mineralizer is composed of WO3 and Bi2O3. This application starts with reducing the magnetocrystalline anisotropy of the power manganese-zinc ferrite material to improve the low-temperature power consumption characteristics of the material. The main formula adopts an iron formula, combined with doped oxides Co2O3, TiO2, and SnO2 that can improve magnetocrystalline anisotropy, to achieve the improvement of the low-temperature magnetocrystalline anisotropy constant of the power manganese-zinc ferrite material, thereby effectively reducing the low-temperature power consumption characteristics. The oxides that improve magnetocrystalline anisotropy in doping and the oxides that improve resistivity are matched with each other, and used in conjunction with mineralizers, which can simultaneously reduce the hysteresis loss and eddy current loss of the material, thereby effectively reducing the total power consumption of the material and achieving low temperature and low power consumption effects. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0029] Figure 1 The power loss-temperature characteristic curve of soft ferrite materials for new energy vehicles;

[0030] Figure 2 This is the characteristic curve of the change of magnetic permeability of low-power ferrite material PC95 with temperature;

[0031] Figure 3 This is the graph showing the variation of the magnetocrystalline anisotropy constant K1 of ferrite material with temperature;

[0032] Figure 4 This is a flow chart of the preparation method of the low-temperature and low-power consumption manganese-zinc ferrite material in the embodiments provided in this application. DETAILED DESCRIPTION

[0033] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.

[0034] Manganese zinc ferrite is widely used in various electronic devices such as transformers, inductors, switching power supplies, filters, power dividers, couplers, antennas, sensors, etc. due to its high magnetic permeability, high saturation flux density Bs and low power loss. As a widely used basic electronic material, manganese zinc ferrite plays an indispensable role in the power conversion process of electric vehicles. It is widely used in new energy vehicle OBC equipment, EV charging equipment, HEV system power conversion, DC-DC converters, battery management systems, power distribution units, etc. The performance of manganese zinc ferrite is often no longer required to have a single indicator, such as low power consumption or high magnetic permeability; higher requirements are put forward for the temperature performance of such devices, especially in order to adapt to cold environments such as northern my country, such as requiring the device to work normally in an environment of -40C to 120°C.

[0035] In a low temperature environment, the magnetic permeability of manganese-zinc ferrite will drop significantly due to the influence of the material's magnetocrystalline anisotropy, and the hysteresis loss will increase significantly. Figure 1 , the manganese-zinc ferrite materials in the related technology maintain very low losses at 20-140°C. However, after the temperature is lower than 20°C, the loss of the material begins to increase significantly, and after the temperature reaches below 0°C, the loss increases sharply. For new energy vehicles working in cold areas, their operating temperature deviates from 25-140°C, reaching -30°C or even -40°C. At such a low temperature, the loss of conventional power ferrite materials is very high, and new energy vehicles using such materials are difficult to start, and the vehicles have great safety hazards. Therefore, it is necessary to reduce the power consumption of manganese-zinc ferrite at low temperatures to ensure the working stability of new energy vehicles at extremely low temperatures.

[0036] Based on this, the present application provides a low-temperature and low-power manganese-zinc ferrite material and a preparation method thereof. The present application starts from reducing the magnetocrystalline anisotropy of the power manganese-zinc ferrite material to improve the low-temperature power consumption characteristics of the material. The main formula adopts an iron formula, combined with doped oxides Co2O3, TiO2, and SnO2 that can improve magnetocrystalline anisotropy, to achieve the improvement of the low-temperature magnetocrystalline anisotropy constant of the power manganese-zinc ferrite material, thereby effectively reducing the low-temperature power consumption characteristics. The oxides that improve magnetocrystalline anisotropy in doping and the oxides that improve resistivity are matched with each other, and used in conjunction with mineralizers, which can simultaneously reduce the hysteresis loss and eddy current loss of the material, thereby effectively reducing the total power consumption of the material and achieving low-temperature and low-power consumption effects.

[0037] In some embodiments, the present application provides a low-temperature and low-power manganese-zinc ferrite material, which is composed of a main component, an auxiliary component and a mineralizer; the main component is in molar percentage: 53.5-55.5% Fe2O3, 8.5-11.5% ZnO, and the remainder is Mn3O4, totaling 100%; the auxiliary component is composed of CaO, SiO2, Nb2O5, Co2O3, TiO2, and SnO2. Based on the total weight of the main components, the auxiliary components are in mass percentage: CaO is 0.01-0.05%, SiO2 is 0.05-0.1%, Nb2O5 is 0.01-0.03%, Co2O3 is 0.3-0.6%, TiO2 is 0.05-0.1%, and SnO2 is 0.05-0.1%; the mineralizer is composed of WO3 and Bi2O3.

[0038] For zinc-manganese ferrite materials, the power consumption Pcv is divided into three parts, including hysteresis loss Ph, eddy current loss Pe and residual loss Pr. The current application frequency of conventional power ferrite materials is 50KHZ~200KHz. The residual loss at this frequency is very small and can be ignored. Therefore, reducing the loss of power ferrite materials needs to start with hysteresis loss Ph and eddy current loss Pe. Eddy current loss is a phenomenon in which materials exist in alternating electromagnetic fields. Eddy currents also exist in magnetic materials, causing energy loss in the magnetic core and causing the magnetic core to heat up. The loss caused by eddy currents is called eddy current loss. At different temperatures, the proportion of hysteresis loss and eddy current loss is different. At room temperature, for power ferrite materials with an application frequency of about 100kHz, the hysteresis loss accounts for nearly 80%, and the eddy current loss accounts for about 20%. As the test temperature increases, the proportion of eddy current loss also increases. At 120℃, the hysteresis loss accounts for about 40%, and the eddy current loss accounts for about 60%. Therefore, for power ferrite materials, the loss composition at -40℃~25℃ is hysteresis loss, and eddy current loss accounts for a relatively small proportion. Improving the low-temperature power consumption characteristics of power ferrite materials requires reducing the hysteresis loss Ph.

[0039] Hysteresis loss Ph originates from the irreversible magnetization process of magnetic materials and is proportional to the area of ​​the hysteresis loop. To reduce hysteresis loss, it is necessary to increase the magnetic permeability μi of the material. The characteristics of the magnetic permeability of conventional wide-temperature, low-power ferrite material PC95 changing with temperature are as follows: Figure 2 As shown, this type of material has a higher initial magnetic permeability above 0°C, but below 0°C, the initial magnetic permeability drops sharply. Correspondingly, the hysteresis loss Ph of this type of material below 0°C is also very high, so the total loss is also high.

[0040] The initial magnetic permeability μi of ferrite material has the following relationship with the saturation magnetization Ms, magnetocrystalline anisotropy constant K1, hysteresis expansion coefficient λs, and stress σ:

[0041]

[0042] like Figure 3 As shown, the initial magnetic permeability μi of the ferrite material is inversely proportional to the absolute value of the magnetocrystalline anisotropy constant |K1|. The smaller |K1| is, the higher the corresponding magnetic permeability μi is.

[0043] At low temperatures, the magnetocrystalline anisotropy constant K1 of ferrite materials is a low negative value, |K1| is relatively high, and the corresponding magnetic permeability is low and the power consumption is also high. This is also the fundamental reason for the high low-temperature loss of power ferrite materials. In order to reduce the low-temperature loss characteristics of this type of material, its |K1| at low temperatures must be reduced.

[0044] Manganese-zinc ferrite materials are mainly made of iron oxide (Fe2O3), manganese tetraoxide (Mn3O4), and zinc oxide (ZnO). During the secondary high-temperature sintering stage, the three raw materials react to form spinel structures of Fe3O4, MnFe2O4, and ZnFe2O4. In this way, Fe 2+ , Fe 3+ , Mn 2+ 、Zn 2+ Among these ions, only Fe 2+ It has positive magnetocrystalline anisotropy, while the other three cations have negative magnetocrystalline anisotropy. In order to reduce the magnetocrystalline anisotropy |K1| of ferrite materials at low temperatures, it is necessary to use an iron formula to prepare such materials, so that the material can form a sufficient amount of Fe after sintering. 2+ , to effectively compensate for the negative low-temperature anisotropy of the material, thereby reducing |K1|.

[0045] Since some metal oxide ions have negative magnetocrystalline anisotropy relative to manganese-zinc ferrite materials, these doping can effectively improve the wide temperature magnetocrystalline anisotropy of the material and improve the material performance. These metal oxide ions are mainly composed of Co 2+ 、Ti 4+ Sn 4+ Among them, Co 2+ It is a commonly used dopant in power ferrite materials. It can effectively improve the wide temperature magnetocrystalline anisotropy of ferrite materials, thus making them have excellent wide temperature and low power consumption characteristics. 2+ It also has a very good effect on improving the low-temperature magnetocrystalline anisotropy of ferrite materials and is an essential dopant for preparing low-temperature and low-power ferrite materials. 4+ and Sn 4+ With Co 2+ It also has a similar effect. Combining these three metal oxides can achieve very good results in reducing low-temperature power consumption characteristics.

[0046] For another type of power manganese-zinc ferrite material, commonly used dopants to improve power consumption, such as SiO2, CaO, Nb2O5, and ZrO2, the main function of these dopants is to aggregate and segregate at the grain boundaries of the material during the sintering stage to form a high-resistivity insulating layer, thereby reducing the eddy current loss characteristics of the material. Since the high-temperature loss of power ferrite materials is mainly composed of eddy current losses, this type of doping can effectively improve the high-temperature power consumption characteristics of the material. On the other hand, these oxides are segregated at the grain boundaries as heterogeneous phases, which increases the thickness of the grain boundary layer and hinders the movement of the magnetic domain wall, so they will also greatly reduce the magnetic permeability of the material and increase the hysteresis loss, among which Nb2O5, ZrO2 and other oxides are particularly obvious. The low-temperature loss of power ferrite materials is mainly hysteresis loss, so this type of oxide doping is not conducive to the low-temperature power consumption characteristics. If this type of dopant is not used, the grain boundary resistivity of the prepared ferrite material is very low, the low-temperature eddy current loss of the material will also increase sharply, and the low-temperature power consumption characteristics will also deteriorate. Therefore, this type of dopant cannot be absent, but the doping amount must be small, and the deterioration effect on the magnetic permeability must be as small as possible. The effect of deterioration of magnetic permeability is much smaller when only CaO, SiO2 and Nb2O5 are used, and the effect of improving resistance is also very obvious, and the doping amount is as small as possible. The best low-temperature power consumption characteristics can be achieved by combining with oxides such as Co2O3, TiO2, SnO2, etc. that improve low-temperature magnetocrystalline anisotropy.

[0047] This application starts with reducing the magnetocrystalline anisotropy of the power manganese-zinc ferrite material to improve the low-temperature power consumption characteristics of the material. The main formula adopts an iron formula, combined with doped oxides Co2O3, TiO2, and SnO2 that can improve magnetocrystalline anisotropy, to achieve the improvement of the low-temperature magnetocrystalline anisotropy constant of the power manganese-zinc ferrite material, thereby effectively reducing the low-temperature power consumption characteristics.

[0048] In some possible implementations, based on the total weight of the main components, the mineralizers are in the following mass percentages: WO3 is 0.01-0.05%, and Bi2O3 is 0.02-0.06%.

[0049] In the process of preparing manganese-zinc ferrite materials, the application adds some mineralizers to increase the active polarization of ions, promote the ferrite sintering reaction and grain growth, and improve the initial magnetic permeability of the material. Adding a small amount of WO3 and Bi2O3 to manganese-zinc ferrite can promote the growth of grains within a certain sintering range, which is beneficial to improve the magnetic permeability and reduce the hysteresis loss of the material.

[0050] Doping oxides that improve magnetocrystalline anisotropy and oxides that improve resistivity are combined with mineralizers to reduce both the hysteresis loss and eddy current loss of the material, thereby effectively reducing the total power consumption of the material and achieving low temperature and low power consumption effects.

[0051] like Figure 4 As shown, in some embodiments, the present application provides a method for preparing a low-temperature and low-power consumption manganese-zinc ferrite material, the preparation method comprising:

[0052] Weigh iron oxide, manganese tetraoxide and zinc oxide, put them into a sand mill, add deionized water, mix and dry to obtain a mixed dry material;

[0053] The mixed dry material is subjected to high temperature roasting, and the mixed dry material after high temperature roasting is mixed with auxiliary components and a mineralizer to obtain a sand-grinding powder, and the sand-grinding powder is put into a sand mill to obtain a sand-grinding slurry;

[0054] The sanding slurry is mixed with a binder, spray granulated and pressed to obtain a blank;

[0055] Pre-sintering the blank;

[0056] The pre-sintered blank is sintered to obtain a sintered material, and the sintered material is subjected to a two-step atmosphere treatment method for heat preservation to obtain a manganese-zinc ferrite material.

[0057] For power ferrite materials, sintering is an important process that determines the material properties. The ferrite material is treated with a balanced atmosphere during the sintering, heat preservation and cooling stages. The relationship between the sintering atmosphere and the treatment temperature is as follows:

[0058]

[0059] Where PO2 is the oxygen content of the sintering atmosphere, a is the atmosphere parameter, the value is between 6-9, b is a constant, b=14540, T is the absolute temperature; different values ​​of the atmosphere parameter a correspond to different sintering atmosphere oxygen contents. The higher the a value is set, the higher the oxygen content of the sintering atmosphere is, and vice versa.

[0060] Power manganese-zinc ferrite materials generally use an iron-excess formula, that is, the amount of Fe2O3 in the main formula is relatively high, most of the Fe2O3 reacts with the raw materials Mn3O4 and ZnO to form MnFe2O4 and ZnFe2O4, and a part of Fe2O3 remains. During the sintering and heat preservation stage, if the oxygen content of the atmosphere is low enough, the remaining Fe2O3 will be reduced to Fe3O4, that is, a certain amount of Fe 2+ By controlling the oxygen content of the sintering atmosphere, Fe 2+ The formation quantity improves the low-temperature anisotropy of the material and reduces the power consumption characteristics. For power ferrite materials with low temperature and low power consumption, the use of a partial reduction sintering atmosphere treatment is beneficial to product performance.

[0061] Wherein, the pre-sintering of the blank comprises:

[0062] The pressed blank is pre-sintered in an atmosphere protection bell furnace, wherein during the pre-sintering process, the temperature is raised to 200° C. at a rate of 1 to 4° C. / min, and then raised to 300 to 350° C. at a rate of 0.5 to 1° C. / min.

[0063] The polyvinyl alcohol (PVA) added in the granulation process will decompose and volatilize at 200-300°C. If the temperature rises too quickly at this stage, the PVA will volatilize violently, which may easily cause the blank to crack. Therefore, the temperature needs to be raised slowly at 200-350°C to ensure that the PVA has sufficient time to volatilize.

[0064] The pre-sintered blank is sintered to obtain a sintered material including:

[0065] When the pre-sintered blank is sintered, the temperature in the atmosphere protection bell furnace is raised to 1100-1150° C. at a heating rate of 2-4° C. / min;

[0066] In a nitrogen atmosphere with an oxygen content of 0.01 to 0.05%, the temperature in the atmosphere protection bell furnace is raised to 1250 to 1350° C. at a heating rate of 4 to 8° C. / min;

[0067] After the temperature reaches 1250-1350°C, keep it warm for 2-4 hours in a nitrogen atmosphere with an oxygen content of 0.005-0.01%;

[0068] The oxygen content of the atmosphere protection bell furnace is adjusted, and the temperature is kept in a nitrogen atmosphere with an oxygen content of 2 to 5% for 1 to 3 hours.

[0069] In the first stage, the heat preservation atmosphere is treated to a relatively low temperature, and sintering is carried out in a reducing atmosphere. The excess Fe2O3 in the raw materials can fully react to become Fe3O4, thereby forming an appropriate amount of Fe 2+ , reducing the low temperature loss of materials. On the other hand, Fe 2+ The formation of will reduce the resistivity of manganese-zinc ferrite materials, increase eddy current loss, and is not good for the total loss. In the late and warm-keeping stages, adjust the oxygen content to be consistent with the equilibrium atmosphere, and reduce the Fe 2+ Oxidized to Fe 3+ , hindering the electrons from flowing into Fe 2+ and Fe 3+ Through this treatment method, a power ferrite material with low hysteresis loss and eddy current loss can be obtained.

[0070] The sintering material is treated with a two-step atmosphere treatment method including:

[0071] After the insulation is completed, the temperature in the atmosphere protection bell furnace is reduced to 1000°C to 1100°C at a cooling rate of 0.3 to 1.0°C / min; wherein the oxygen content of the atmosphere corresponding to 1100°C is 0.3 to 0.6%, the oxygen content of the atmosphere corresponding to 1050°C is 0.05 to 0.1%, and the oxygen content of the atmosphere corresponding to 1000°C is 0.02 to 0.05%;

[0072] When the temperature in the atmosphere protection bell furnace reaches 1000°C to 1100°C, the temperature in the atmosphere protection bell furnace is cooled to 200°C at a cooling rate of 5 to 10°C / min in a nitrogen atmosphere with an oxygen content of less than 50 ppm.

[0073] The main purpose of reducing the oxygen content of the sintering atmosphere at 1050℃ and 1000℃ is to avoid oxidation of MnFe2O4 and Fe3O4 formed during the insulation stage, which deteriorates the material properties. In a nitrogen atmosphere with an oxygen content of less than 50ppm, the purpose of cooling the sintering atmosphere is also to protect the MnFe2O4 and Fe3O4 formed during the insulation stage and avoid damage to the material properties.

[0074] In some embodiments, the temperature for high-temperature calcination of the mixed dry material is 850-950° C., and the high-temperature calcination time is 1-4 hours.

[0075] In some embodiments, the weight of deionized water added to the sand mill is 50-100% of the weight of the sand-grinding powder, the sand-grinding time is 2-4 hours, and the laser particle size D50 of the sand-grinding powder is about 1.0-1.5 μm.

[0076] In some embodiments, the binder is polyvinyl alcohol, and the polyvinyl alcohol accounts for 0.1% to 0.5% of the weight of the sanding slurry.

[0077] In some embodiments, the blank density is 3.0-3.2 kg / cm 3 .

[0078] The preparation method of the low-temperature and low-power consumption manganese-zinc ferrite material provided in the present application adopts a two-step atmosphere treatment method for heat preservation during sintering, wherein a reducing atmosphere is used in the early stage of heat preservation, and a balanced atmosphere is used in the late stage of heat preservation and the cooling stage. The Fe inside the grains of the material obtained by sintering in this process is 2+ More, Fe at the grain boundary 3+ Such materials have both high magnetic permeability and high resistivity, and have good low-temperature power consumption characteristics.

[0079] The present invention is further described below in conjunction with specific embodiments.

[0080] Example 1

[0081] (1) According to the ratio (Fe2O3: 53.5mol%, ZnO: 8.5mol%, the balance is Mn3O4), accurately weigh 704g of raw materials of iron oxide red, 239g of Mn3O4 and 57g of ZnO, put them into a sand mill, add 50-100% of the weight of the raw materials in deionized water and mix them for 30-90min. The mixed raw materials are dried in an oven at 110-200°C for 12-18h.

[0082] (2) The mixed dried material is placed in a muffle furnace for pre-burning at a temperature of 850-950°C for 1 to 4 hours.

[0083] After the pre-burned material is cooled sufficiently, it is put into a sand mill and the auxiliary components are accurately weighed according to the weight of the pre-burned material. The auxiliary components are in percentage by mass: CaO: 0.01%, SiO2: 0.01%, Co2O3: 0.3%, TiO2: 0.05%, SnO2: 0.05%, mineralizer WO3: 0.01%, and Bi2O3: 0.02%.

[0084] Add the auxiliary components into the sand mill, add 50-100% of the weight of the sand mill powder in deionized water, and perform sand milling for 2-4 hours. The laser particle size D50 of the sand mill powder is about 1.0-1.5 μm.

[0085] (3) Add 0.1-0.5% of the weight of the ferrite pre-sintered material as a polyvinyl alcohol (PVA) binder to the sand abrasive slurry and perform spray granulation.

[0086] (4) The granulated ferrite material is pressed into a blank with a density of 3.0 to 3.2 kg / cm 3 .

[0087] (5) Sintering the pressed blank in an atmosphere-protected bell furnace, and the sintering process is as follows:

[0088] ①In air, increase the temperature to 200℃ at a rate of 0.5~4℃ / min, and then increase the temperature to 300~350℃ at a rate of 0.5~1℃ / min.

[0089] ② Directly heat to 1100-1150℃ at a speed of 2-6℃ / min, the oxygen content of the sintering atmosphere is reduced to 0.5-5.0%, and then heat to 1250-1350℃ at a speed of 4-8℃ / min. The oxygen content of the atmosphere at this stage is 0.01-0.05%. After heating to 1250-1350℃, keep warm for 2-4h. The oxygen content of the atmosphere at this stage is 0.005-0.01%. Then continue to keep warm for 1-3h, and the oxygen content is 2-5%.

[0090] ③ After the insulation is completed, reduce the temperature to 1000℃ at a rate of 0.3~1.0℃ / min. The oxygen content at 1100℃ is controlled at 0.3~0.6%, the oxygen content at 1050℃ is controlled at 0.05~0.1%, and the oxygen content at 1000℃ is controlled at 0.02~0.05%.

[0091] ④ Cool down to 200°C at a cooling rate of 5-10°C / min, control the oxygen content of the atmosphere below 50ppm, and obtain the manganese-zinc ferrite material after annealing.

[0092] Example 2

[0093] The preparation method is the same as that of Example 1, except that the raw material ratio is different. (Fe2O3: 53.5mol%, ZnO: 11.5mol%, the balance is Mn3O4. The auxiliary components are as follows by mass percentage: CaO: 0.05%, SiO2: 0.1%, Nb2O5: 0.03%, Co2O3: 0.6%, TiO2: 0.1%, SnO2: 0.1%, mineralizer WO3: 0.05%, Bi2O3: 0.06%.).

[0094] Example 3

[0095] The preparation method is the same as that of Example 1, except that the raw material ratio is different. (Fe2O3: 54.5mol%, ZnO: 10mol%, and the balance is Mn3O4. The auxiliary components are as follows by mass percentage: CaO: 0.03%, SiO2: 0.06%, Nb2O5: 0.01%, Co2O3: 0.5%, TiO2: 0.06%, SnO2: 0.07%, mineralizer WO3: 0.03%, Bi2O3: 0.04%.).

[0096] Example 4

[0097] The preparation method is the same as that of Example 1, except that the raw material ratio is different. (Fe2O3: 54mol%, ZnO: 11mol%, and the balance is Mn3O4. The auxiliary components are as follows by mass percentage: CaO: 0.04%, SiO2: 0.07%, Nb2O5: 0.02%, Co2O3: 0.4%, TiO2: 0.07%, SnO2: 0.08%, mineralizer WO3: 0.02%, Bi2O3: 0.05%.).

[0098] The manganese-zinc ferrite material of Example 1 was prepared into samples 1 to 4 in turn, and the performance thereof was tested using a T 25mm×15mm×10mm sample ring, f=100KHz, Bm=200mT, and the power consumption is shown in the following table:

[0099] Table 1

[0100]

[0101] As can be seen from Table 1, the power consumption of the manganese-zinc ferrite material prepared in this application at a temperature of -40°C to 0°C is significantly lower than that of the currently commonly used power ferrite material PC95, and the wide temperature power consumption characteristics, especially the low temperature power consumption characteristics, are particularly prominent.

[0102] The manganese-zinc ferrite material of Example 1 was sequentially prepared into samples 1 to 4, and performance tests were performed on them. The magnetic permeability results are shown in Table 2.

[0103] Table 2

[0104]

[0105] It can be seen from the above embodiments that the present application provides a low-temperature and low-power manganese-zinc ferrite material and a preparation method thereof. The manganese-zinc ferrite material includes a main component, an auxiliary component and a mineralizer; the main component is in molar percentage: 53.5-55.5% Fe2O3, 8.5-11.5% ZnO, and the remainder is Mn3O4, totaling 100%; the auxiliary components include CaO, SiO2, Nb2O5, Co2O3, TiO2, and SnO2. Based on the total weight of the main components, CaO is 0.01-0.05%, SiO2 is 0.05-0.1%, Nb2O5 is 0.01-0.03%, Co2O3 is 0.3-0.6%, TiO2 is 0.05-0.1%, and SnO2 is 0.05-0.1%; the mineralizer includes WO3 and Bi2O3. This application starts with reducing the magnetocrystalline anisotropy of the power manganese-zinc ferrite material to improve the low-temperature power consumption characteristics of the material. The main formula adopts an iron formula, combined with doped oxides Co2O3, TiO2, and SnO2 that can improve magnetocrystalline anisotropy, to achieve the improvement of the low-temperature magnetocrystalline anisotropy constant of the power manganese-zinc ferrite material, thereby effectively reducing the low-temperature power consumption characteristics. The oxides that improve magnetocrystalline anisotropy in doping and the oxides that improve resistivity are matched with each other, and used in conjunction with mineralizers, which can simultaneously reduce the hysteresis loss and eddy current loss of the material, thereby effectively reducing the total power consumption of the material and achieving low temperature and low power consumption effects.

[0106] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.

Claims

1. A low-temperature and low-power consumption manganese-zinc ferrite material, characterized in that: The manganese-zinc ferrite material consists of a main component, an auxiliary component and a mineralizer; the main component is in molar percentage: 53.5-55.5% Fe2O3, 8.5-11.5% ZnO, and the balance is Mn3O4, totaling 100%; the auxiliary component is composed of CaO, SiO2, Nb2O5, Co2O3, TiO2, and SnO2. Based on the total weight of the main components, the auxiliary components are in mass percentage: CaO is 0.01-0.05%, SiO2 is 0.05-0.1%, Nb2O5 is 0.01-0.03%, Co2O3 is 0.3-0.6%, TiO2 is 0.05-0.1%, and SnO2 is 0.05-0.1%; the mineralizer is composed of WO3 and Bi2O3.

2. The manganese-zinc ferrite material according to claim 1, characterized in that: Based on the total weight of the main components, the mineralizer is in the following mass percentages: WO3 is 0.01-0.05%, and Bi2O3 is 0.02-0.06%.

3. The method for preparing the low-temperature and low-power consumption manganese-zinc ferrite material according to claim 1 or claim 2, characterized in that: The preparation method comprises: Weigh iron oxide, manganese tetraoxide and zinc oxide, put them into a sand mill, add deionized water, mix and dry to obtain a mixed dry material; The mixed dry material is subjected to high temperature roasting, and the mixed dry material after high temperature roasting is mixed with auxiliary components and a mineralizer to obtain a sand-grinding powder, and the sand-grinding powder is put into a sand mill to obtain a sand-grinding slurry; The sanding slurry is mixed with a binder, spray granulated and pressed to obtain a blank; Pre-sintering the blank; The pre-sintered blank is sintered to obtain a sintered material, and the sintered material is subjected to a two-step atmosphere treatment method for heat preservation to obtain a manganese-zinc ferrite material.

4. The preparation method according to claim 3, characterized in that: The pre-sintering of the blank comprises: The pressed blank is pre-sintered in an atmosphere protection bell furnace, wherein the temperature is raised to 200°C at a heating rate of 1-4°C / min and then raised to 300-350°C at a heating rate of 0.5-1°C / min.

5. The preparation method according to claim 3, characterized in that: The pre-sintered blank is sintered to obtain a sintered material including: When the pre-sintered blank is sintered, the temperature in the atmosphere protection bell furnace is raised to 1100-1150° C. at a heating rate of 2-4° C. / min; After the temperature reaches 1100-1150° C., in a nitrogen atmosphere with an oxygen content of 0.01-0.05%, the temperature in the atmosphere protection bell furnace is raised to 1250-1350° C. at a heating rate of 4-8° C. / min; After the temperature reaches 1250-1350°C, keep it warm for 2-4 hours in a nitrogen atmosphere with an oxygen content of 0.005-0.01%; The oxygen content of the atmosphere protection bell furnace is adjusted, and the temperature is kept in a nitrogen atmosphere with an oxygen content of 2 to 5% for 1 to 3 hours.

6. The preparation method according to claim 3, characterized in that: The sintering material is treated with a two-step atmosphere treatment method including: After the insulation is completed, the temperature in the atmosphere protection bell furnace is reduced to 1000°C to 1100°C at a cooling rate of 0.3 to 1.0°C / min; wherein the oxygen content of the atmosphere corresponding to 1100°C is 0.3 to 0.6%, the oxygen content of the atmosphere corresponding to 1050°C is 0.05 to 0.1%, and the oxygen content of the atmosphere corresponding to 1000°C is 0.02 to 0.05%; When the temperature in the atmosphere protection bell furnace reaches 1000°C to 1100°C, the temperature in the atmosphere protection bell furnace is cooled to 200°C at a cooling rate of 5 to 10°C / min in a nitrogen atmosphere with an oxygen content of less than 50 ppm.

7. The preparation method according to claim 3, characterized in that: The temperature for high-temperature roasting of the mixed dry material is 850-950° C., and the high-temperature roasting time is 1-4 hours.

8. The preparation method according to claim 3, characterized in that: The weight of deionized water added to the sand mill is 50-100% of the weight of the sand-milled powder, the sand-milling time is 2-4 hours, and the laser particle size D50 of the sand-milled powder is about 1.0-1.5 μm.

9. The preparation method according to claim 3, characterized in that: The binder is polyvinyl alcohol, and the amount of the polyvinyl alcohol is 0.1% to 0.5% of the weight of the sanding slurry.

10. The preparation method according to claim 3, characterized in that: The blank density is 3.0-3.2 kg / cm 3 .

Citation Information

Patent Citations

  • Manganese zinc ferrite of high magnetic conductivity high saturation magnetic flux density high Curie temperature

    CN101388269A

  • Method for manufacturing low-loss manganese-zinc ferrite

    CN104310983A

  • High-performance manganese zinc ferrite material and preparing method thereof

    CN109608185A

  • Ultra-low-loss high-Bs wide-temperature broadband manganese zinc ferrite material and preparation method thereof

    CN117843357A

  • Method of regenerating manganese-zinc ferrite

    JP2004217519A

Cited By

  • Manganese zinc ferrite material with low loss of-30 to 150 DEG C and preparation method thereof

    CN121651909A